Equid herpesvirus type 3 infection produces membrane-associated and secreted forms of glycoprotein G that are not required for efficient cell-to-cell spread of the virus in vitro - Losinno, Antonella; Vissani, Maria Aldana; Sanchez, Diego; Damiani, Armando Mario (Springer, 2023)
The ORF 70 gene of equid alphaherpesvirus type 3 (EHV-3) encodes glycoprotein G (gG), which is conserved in the majority of alphaherpesviruses. This glycoprotein is located in the viral envelope and has the characteristic of being secreted into the culture medium after proteolytic processing. It modulates the antiviral immune response of the host by interacting with chemokines. The aim of this study was to identify and characterize EHV-3 gG. By constructing viruses with HA-tagged gG, it was possible to detect gG in lysates of infected cells, their supernatants, and purified virions. A 100-, 60-, and 17-kDa form of the protein were detected in viral particles, while a 60-kDa form was identified in supernatants of infected cells. The role of EHV-3 gG in the viral infection cycle was assessed by the construction of a gG-minus EHV-3 mutant and its gG-positive revertant. When growth characteristics in an equine dermal fibroblast cell line were compared, the plaque size and the growth kinetics of the gG-minus mutant were similar to those of the revertant virus, suggesting that EHV-3 gG does not play a role in direct cell-to-cell transmission or virus proliferation of EHV-3 in tissue culture. The identification and characterization of EHV-3 gG described here provide a solid background for further studies to assess whether this glycoprotein has a function in modulating the host immune response.